2021
DOI: 10.2147/rmhp.s312148
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Sources of Information About Immunization as Predictors of Delayed Childhood Vaccinations in Saudi Arabia During the COVID-19 Pandemic: A Cross-Sectional Questionnaire Study

Abstract: Purpose This study compared the most used sources of information by caregivers for scheduled childhood vaccination in Saudi Arabia before and during the COVID-19 pandemic and examined the effect of this decision-making. Methods An electronic survey was administered to 577 caregivers of children aged ≤2 years residing in Saudi Arabia during the COVID-19 pandemic curfew. The sources of information on childhood vaccination considered by the caregivers and their influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…These findings are also consistent with those reported in other Italian studies during the pre-pandemic period [23,49,50] and represent a noteworthy trend, since scientific literature recognises these sources as primary contributors to mis-information [51][52][53][54]. Moreover, a study conducted in Saudi Arabia reported that seeking vaccination information from family, friends, or social media increased delayed vaccinations [55]. The results indicate that the overall perceived usefulness of the internet, whether specifically referring to institutional or non-institutional websites or to mobile applications, is supported by previous studies that recognise it as one of the primary sources of information [56,57].…”
Section: Sources Of Informationsupporting
confidence: 90%
“…These findings are also consistent with those reported in other Italian studies during the pre-pandemic period [23,49,50] and represent a noteworthy trend, since scientific literature recognises these sources as primary contributors to mis-information [51][52][53][54]. Moreover, a study conducted in Saudi Arabia reported that seeking vaccination information from family, friends, or social media increased delayed vaccinations [55]. The results indicate that the overall perceived usefulness of the internet, whether specifically referring to institutional or non-institutional websites or to mobile applications, is supported by previous studies that recognise it as one of the primary sources of information [56,57].…”
Section: Sources Of Informationsupporting
confidence: 90%
“…Inclination towards SMPs to seek information on vaccines during the COVID-19 pandemic played a significant role in parents' decision-making on children's immunization in countries like Saudi Arabia and Israel. 53 54 A study was conducted on 577 caregivers of children aged < 2 years in Saudi Arabia to assess the predictors of delayed vaccine. Searching online for vaccine-related information or taking others' opinions was preferred by only 1% of respondents before the pandemic, but increased to 30% during the pandemic.…”
Section: Challenges In Administering Non-covid-19 Immunizationmentioning
confidence: 99%
“…The use of SMPs was also associated with increased fear of vaccines and increased odds of delayed vaccination by 3–4 times. 53 Ashkenazi et al 54 concluded in a study evaluating measles vaccine hesitancy that the vaccination status was significantly associated with the primary source of information used for making decision. About 85% of parents acquiring knowledge from family physicians or paediatricians vaccinated their children, whereas half of the parents whose most trusted source was the internet or SMPs were vaccine hesitant.…”
Section: Challenges In Administering Non-covid-19 Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Baghdadi et al (2022) revealed that caregivers' health-information seeking behavior was oriented toward social media networking throughout the pandemic, social media, particularly YouTube and Facebook, influenced parents' decisions about their children's immunizations, primarily in Saudi Arabia [9]. The assessment outcomes shed light on the best ways to reach the Saudi public and launch a successful awareness campaign by identifying the most popular and powerful information resources.…”
Section: Saudi Parents' Views On the Covid-19 Vaccinementioning
confidence: 99%